(untitled) (Journal of Economic Research & Business Administration, 2016)
This research is devoted to a problem of determination of PPP in the sphere of environmental protection, to identification of the existing merits and demerits of PPP in Kazakhstan, to search of efficient mechanisms of interaction of the state and business, and preparation of recommendations concerning the prospects of development of this cooperation in the country. Within this, research authors carried out the overview of foreign experience of use of the mechanism of public-private partnership. The purpose of this research is development of theoretical-practical bases of use of the mechanism of public-private partnership and identification of opportunities of its application for the solution of environmental problems in development of economy of Kazakhstan. Despite active use of mechanisms of PPP by Kazakhstan for projects implementation in the sphere of housing and communal services, creation of engineering infrastructure and a construction of social objects, in the ecological sphere these projects are practically not implemented.